LEGAL PRAGMATISM AS A GUIDE TO NEW PERSPECTIVES ON THE APPLICATION OF LAW - Gonzaga, Alvaro de Azevedo; Labruna, Felipe; Mazon, Cassiano (Revista da Faculdade de Direito do Sul de Minas, 2024)
This is an article about Legal Pragmatism, studied under the prism of the Philosophy of Law. The pragmatist philosophical current, born in the United States, was responsible for consolidating the line of legal reasoning aimed at obtaining the results that best meet social desires and human hopes. Legal Pragmatism is not presented as a Theory of Law, consubstantiating itself, in reality, in a method based on argumentation, capable of substantiating decision making. Finally, an attempt was made to ponder on Legal Pragmatism in the Brazilian legal system, as a guide for new perspectives on the application of Law, with emphasis on the recent changes in the Law of Introduction to the Rules of Brazilian Law (Lei de Introdução às Normas do Direito Brasileiro).